Biomechanical study on the treatment of tibial defects in total knee arthroplasty using the cement-screw and metal block with extension stem techniques: a finite element analysis - Lu, Yafei; Tang, Zhongjian; Gu, Qiang; Zhu, Zhexi; Liu, Wenrui; Zhu, Ziqiang; Duan, Gang (Frontiers in Bioengineering and Biotechnology, 2026)
ObjectiveTo compare the biomechanical properties of the cement-screw technique with the metal block extension stem technique in reconstructing Anderson Orthopaedic Research Institute (AORI) type 2 tibial defects in total knee arthroplasty using the finite element method, in order to provide a basis for clinical selection.MethodsNon-inclusive 5-mm and 10-mm depth AORI type 2 tibial defects were modeled using the finite element method. The cement-screw technique and the metal block extension stem technique were applied for reconstruction, resulting in a total of four sets of finite element models. Each group of models was tested under two loads: horizontal walking and descending stairs. The von Mises stress distributions in the tibia, prosthesis, and bone defect regions, as well as the peaks of micromotion at the prosthesis-tibia interface, were measured.ResultsIn the AORI type 2 tibial defect model, the cement-screw group, when reconstructing 5 mm and 10 mm defects under horizontal walking and descending stairs loads, exhibited higher maximum tibial stress (5 mm: 78.0–140 MPa; 10 mm: 80.9–151 MPa), proximal tibial defect area stress (5 mm: 11.3–25.3 MPa; 10 mm: 10.8–24.1 MPa), and peak micromotion values (5 mm: 9.90–26.99 μm; 10 mm: 11.94–31.98 μm) compared to the metal block extension stem group (tibial stress 5 mm: 73.2–130 MPa, 10 mm: 66.6–118 MPa; defect area stress 5 mm: 7.83–16.3 MPa, 10 mm: 8.54–18.8 MPa; peak micromotion 5 mm: 6.56–14.72 μm, 10 mm: 8.92–24.09 μm). However, prosthesis stresses were lower in the cement-screw group (5 mm: 87.1–183 MPa; 10 mm: 60.2–158 MPa) than in the metal block extension stem group (5 mm: 101–194 MPa, 10 mm: 92.7–167 MPa). Under horizontal walking loading, the two techniques showed no superiority of one over the other in terms of the von Mises stresses and the peaks of micromotion; however, under descending stairs loads, the maximum stress in the tibia of the cement-screw group with a 10-mm defect exceeded 150 MPa (151 MPa), indicating a potential fracture risk, and the peaks of micromotion was smaller in all models.ConclusionThe findings of this study indicate that the cement-screw technique is more cost-effective and convenient for repairing 5-mm defects and is appropriate for reconstruction of this size. However, when the bone defect reaches 10 mm, the cement-screw technique may elevate the risk of fracture, and thus, safety concerns must be taken into account. In contrast, the metal block extension stem technique offers a better balance between effectiveness and safety, making it the preferred option for defects of this size.